Mozart: Serenade in C minor (Bärenreiter-Verlag Karl Vötterle GmbH & Co. KG, 1979)
This edition of Walofgang Amadeus Mozart´s Serenade in C minor is identical with the Urtext of the ´New Mozart Edition´. With this reliable material reflecting the very latest in Mozart research, players have the opportunity to render performances faithful to the original.